Role of Inflammasomes in Salmonella Infection - Franchi, Luigi (Frontiers in Microbiology, 2011)
Pattern recognition receptors (PRRs) play a crucial role in both the detection of pathogens and the activation of the innate immune system. Nod-like receptors (NLR) family members are cytosolic PRRs that sense bacterial products or endogenous danger signals. Recent evidence suggests that NLRs contribute to the detection of Salmonella through the activation of inflammasomes, molecular platforms that promotes the maturation of the proinflammatory cytokines IL-1β and IL-18. During enteric Salmonella infection the activation of caspase-1 and the production of IL-1β and IL-18 result in a protective host response. In macrophages, the activation of caspase-1 induced by Salmonella is mainly mediated by the NLR family member NLRC4 that senses cytosolic flagellin. Recent data suggest that an effective innate immune response against Salmonella requires the engagement of multiple inflammasomes in both hematopoietic and non-hematopoietic cell lineages. Further understanding of the innate immune response mediated by inflammasomes should provide new insights into the mechanisms of host defense and the pathogenesis of inflammatory diseases.